Nucleic Acids Delivery Into the Cells Using Pro-Apoptotic Protein Lactaptin - Chinak, Olga; Golubitskaya, Ekaterina; Pyshnaya, Inna; Stepanov, Grigory; Zhuravlev, Evgenii; Richter, Vladimir; Koval, Olga (Frontiers in Pharmacology, 2019)
Successful delivery of exogenous DNA and RNA molecules into cells has major implications for gene-based technologies and therapeutic approaches. Since free DNA and RNA are not readily taken up by cells, various delivery systems were developed during the last twenty years (Bolhassani, 2011). Delivery molecules or vesicles help nucleic acids to cross biological barriers and prevent enzymatic degradation by endogenous nucleases. Besides the lipid-based delivery system, the polymer-based delivery system or inorganic nanoparticles, peptide carriers can be also used for nucleic acids transport into the cells (Rathnayake et al., 2017; Zorko and Langel, 2005). Among peptide carriers the most promising are short amphipathic and cationic peptides which translocate themselves across membranes and are collectively named as cell penetrating peptides (CPP) (Hoyer and Neundorf, 2012; Morris and Labhasetwar, 2015). There is no unique classification for CPPs yet and usually they are classified according to their origin, specificity to cargo and amino acid composition. In 1997 Morris et al. demonstrated that 27-residues CPP peptide vector being premixed with single- or double-stranded deoxyoligonucleotides efficiently delivered them into cultured mammalian cells (Morris et al., 1997). Later, two CPPs - transportan and penetratin successfully delivered 21-mer peptide nucleic acid (PNA) complementary to the human galanin receptor type 1 mRNA resulted in the suppression of galanin receptor (Pooga et al., 1998). Thereby CPPs deliver functionally active nucleic acids into the cells. Lactaptin, a 8.6 kDa proteolytic fragment of human milk kappa-casein, selectively kills various tumor cells while it is used in micromole concentration (Koval et al., 2012; Semenov et al., 2010). We have earlier demonstrated that recombinant lactaptin (RL2) penetrates into cells partly through lipid-raft-mediated dynamin-independent pinocytosis and partly through direct penetration across the plasma membrane (Chinak et al., 2016). The comparison of RL2 primary structure and the mechanism of its penetration into the cell suggests that it can be assigned to the CPP. In the present work we analyzed if lactaptin analog forms complexes with nucleic acids and if it acts as a delivery system with no cytotoxic effects.